Inequality and power : the economics of class - Schutz, Eric A., 1947- (Routledge frontiers of political economy., 2011)
This book is about the causes and consequences of economic inequality in the advanced market economies of today. It is common that in market systems people choose their own individual economic destinies, but of course the choices people make are importantly determined by the alternatives available to them: unequal opportunity is the critical determinant of economic disparities. This begs the question; from where do the vast inequalities of opportunity arise? This book theorizes that power and social class are the real crux of economic inequality.